Prevalence of Gestational Diabetes Mellitus among Pregnant Females: Prevalence of Gestational Diabetes Mellitus: Pregnant Females - Anwar, Khalida; Hussain, Asia; Zafar, Abeerah; Muzafar, Sehrish; Shaukat, Rabia; Yasin, Hafsa; Yasin, Tayyaba; Yousaf, Nida (Pakistan Journal of Health Sciences, 2026)
Gestational diabetes mellitus (GDM) is a prevalent pregnancy complication marked by glucose intolerance, which poses significant risks to both maternal and fetal health, including preeclampsia, cesarean delivery, macrosomia, and an increased susceptibility to type 2 diabetes later in life. Objectives: To determine the frequency and prevalence of GDM in pregnant women. Methods: A descriptive cross-sectional study was conducted with 160 pregnant women aged 18-45 years at the University of Lahore Teaching Hospital. Data were collected using a structured questionnaire and clinical measurements, including a 50-gram oral glucose challenge test (GCT), followed by a 100-gram oral glucose tolerance test (OGTT) for those with positive GCT results. Results: The mean age of participants was 27.08 ± 4.35 years, with a majority being well-educated (57.9% graduates, 35.2% with master’s degrees, and 1.3% with an MBBS). Most women were housewives (50.3%), followed by office workers (27%) and teachers (20.1%). The mean BMI was 31.70 ± 6.18, indicating a high prevalence of overweight/obesity. Despite recognizing the seriousness of GDM and the importance of a healthy lifestyle, 27% of participants did not exercise regularly, and 23.8% met the criteria for GDM. Conclusions: The study revealed a high prevalence of GDM, primarily driven by overweight/obesity and physical inactivity.